Early pathogenic colonisers of acute burn wounds: A retrospective review. Issue 8 (December 2017) - Park, Hye-Sung; Pham, Chengde; Paul, Eldho; Padiglione, Alex; Lo, Cheng; Cleland, Heather
Highlights: One third of acute burn wounds were colonised with pathogenic gram-positive and gram-negative bacteria within 24 h of burn. The rate of colonisation of acute burns with gram-negative bacteria is independently associated with the size of burn. Surface swabs are more sensitive than tissue biopsies in detecting the presence of colonisers in burn wounds. Abstract: Background: Early excision of burns reduces the incidence of local and systemic infections caused by colonising microorganisms, and reduces mortality and length of hospital stay. Appropriate antibiotic prophylaxis can reduce the risk of postoperative wound infections and skin graft loss. Antibiotic selection should be based on likely pathogens. However, there are few studies that have investigated the early pathogenic colonisers of acute burn wounds. Aim: To describe pathogenic microorganisms found in acute burns and to make further recommendations on the use of early perioperative prophylactic antibiotics. Methods: All burns patients admitted at the tertiary adult burns centre in Victoria over a 2-year period, who had surface swabs or tissue samples obtained from wounds within 24 h of injury were included in this retrospective cohort study. Pathogenic organisms were examined with respect to patient characteristics, burn characteristics, treatment provided and immediate exposure to environmental contaminants. Results: Nearly one third of burns patients had wounds colonised with pathogenic microorganisms. Gram-negative bacteria were isolated from 52% of these. Staphylococcus aureus was the most common isolate. Pseudomonas and Enterobacter species were the most common gram-negatives. The only independent risk factor associated with early colonisation with gram-negative bacteria was per cent TBSA burn. Conclusion: Increased colonisation of acute burn wounds with pathogenic gram-negative bacteria was associated with increased size of burn.